Motor Function Deficits Following Chronic Prenatal Ethanol Exposure are Linked to Impairments in Insulin/IGF, Notch and Wnt Signaling in the Cerebellum - Tong, Ming (2013)
BACKGROUND: Fetal alcohol spectrum disorder (FASD) is associated with deficits in cerebellar function that can persist through adolescence. Previous studies demonstrated striking inhibition of insulin and insulin-like growth factor (IGF) signaling in ethanol-exposed cerebella. OBJECTIVES: We sought to determine if FASD-induced impairments in motor function were associated with deficits in insulin/IGF signaling in juvenile cerebella. Given the growing evidence that insulin/IGF pathways cross-talk with Notch and Wnt to promote brain development and maturation; we also examined the integrity of canonical Wnt and Notch signaling networks in the brain following chronic prenatal ethanol exposure. METHODS: Pregnant Long Evans rats were fed isocaloric liquid diets containing 0% or 24% ethanol by caloric content from gestation day 6 through delivery. Pups were subjected to rotarod testing on postnatal days (P) 15–16 and sacrificed on P30. Cerebella were used for molecular and biochemical analysis of insulin/IGF-1, canonical Wnt, and Notch signaling mechanisms. RESULTS: Prenatal ethanol exposures impaired rotarod performance, inhibited signaling through insulin and IGF-1 receptors, IRS-1, and Akt, increased activation of GSK-3β, and broadly suppressed genes mediating the canonical Wnt and Notch networks. CONCLUSIONS: Abnormalities in cerebellar function following chronic prenatal ethanol exposure are associated with inhibition of insulin/IGF, canonical Wnt, and Notch networks that cross-talk via GSK-3β. Effective therapeutic measures for FASD may require multi-pronged support of interrelated signaling networks that regulate brain development.